PERDAGANGAN LABI-LABI (Amyda cartilaginea) DI PULAU JAWA BAGIAN TENGAH - , AGUNG PERBOWO, drh. Subeno, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Asiatic softshell turtle (Amyda cartilaginea) is wildlife animals that no protected by Indonesian law, but listed into Appendix II of CITES. Over the past few decades, the trade of this spesies has increased rapidly. This spesies has been reported widley used for consumption, as a pet, traditional medicine, and trading both nationally or internationally. Central Java Province is the one of area that became the main harvesting areas for asiatic softshell turtle and has quota catch of 250 heads / year. The purpose of this research are to identify the trader of the asiatic softshell turtle trade in Central Part of Java Island, knowing asiatic softshell turtle trade in Central Part of Java Island, and find out the range of values asiatic softshell turtle trade in Central Part of Java Island. Methods of data collection in this study was conducted by snow-ball sampling and interviews. Snow-ball sampling method are used to find out who the traders involved in the trade of asiatic softshell turtle. Interviews were conducted with people who do the asiatic softshell turtle trade and technical interviews conducted by using in-depth interviews. Asiatic softshell trader in Central Java consist of large traders, collectors, and hunter.Large traders are traders who have a marketing authorization and permission to catch an asiatic softshell turtle. Marketing authorization is obtained from Central Java Natural Resources Conservation Agency (BKSDA). Collectors are people who form the liaison/ intermediary of large traders with hunter. Hunter is a person who captures an asiatic softshell turtle in nature. Trade flows that occurred in the province of Central Java can be simplified as follows: hunter â collector â large traders. Price asiatic softshell turtle in Central Java are divided into two classes by size weight, <1 kg and >1 kg.